THE INFLUENCE OF WORK ENVIRONMENT, ORGANIZATIONAL CULTURE, AND LEADERSHIP ON EMPLOYEE PERFORMANCE AT WINGSTOP - Diah Refiana; Mohamad Trio Febriyantoro; Zulkifli Zulkifli; Dede Suleman; Fendi Saputra; Totok Suyoto (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study is to analyze the influence of the work environment, organizational culture and leadership on employee performance. The population and sample are 40 employees of Wingstop Pamulang. The data collection method used a questionnaire and the analysis technique used was multiple linear regression using SPSS. The results showed that: The work environment has a positive and insignificant effect on employee performance. Organizational culture has a positive and significant effect on employee performance. Leadership has no positive and significant effect on employee performance